Data from: Contrasting effects of large density changes on relative testes size in fluctuating populations of sympatric vole species - Klemme, Ines; Soulsbury, Carl D.; Henttonen, Heikki (Zenodo, 2014)
Across species, there is usually a positive relationship between sperm competition level and male reproductive effort on ejaculates, typically measured using relative testes size (RTS). Within populations, demographic and ecological processes may drastically alter the level of sperm competition and thus, potentially affect the evolution of testes size. Here, we use longitudinal records (across 38 years) from wild sympatric Fennoscandian populations of five species of voles to investigate whether RTS responds to natural fluctuations in population density, i.e. variation in sperm competition risk. We show that for some species RTS increases with density. However, our results also show that this relationship can be reversed in populations with large-scale between-year differences in density. Multiple mechanisms are suggested to explain the negative RTS–density relationship, including testes size response to density-dependent species interactions, an evolutionary response to sperm competition levels that is lagged when density fluctuations are over a certain threshold, or differing investment in pre- and post-copulatory competition at different densities. The results emphasize that our understanding of sperm competition in fluctuating environments is still very limited. Voles testes length data Excel file containing 5 spreadsheets of vole testes length, body mass and capture date data. testes_length_data.xls Voles testes mass data Subset of data containing testes length and testes mass, body mass and capture date. vole_testesmass.xlsx Voles density data Summer and autumn density data for 5 species of data from 1970 onwards. voles_densities.xls